2014
DOI: 10.1152/ajpcell.00194.2014
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Bifidobacterium species stimulate human SLC26A3 gene function and expression in intestinal epithelial cells

Abstract: SLC26A3, or downregulated in adenoma (DRA), plays a major role in mediating Cl(-) absorption in the mammalian intestine. Disturbances in DRA function and expression have been implicated in intestinal disorders such as congenital Cl(-) diarrhea and gut inflammation. We previously showed that an increase in DRA function and expression by Lactobacillus acidophilus and its culture supernatant (CS) might underlie antidiarrheal effects of this probiotic strain. However, the effects of Bifidobacterium species, import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…Thus, the reductions in urinary oxalate in animals colonized with B. animalis occurred solely by intraluminal oxalate degradation. It is notable here that Kumar et al [176] looked at three other strains of Bifidobacteria and reported an increased expression of DRA in both mice and Caco-2 cells. This work focused on Cl − uptake by Caco-2 monolayers using a surrogate tracer ( 125 I) to show an approximate twofold induction of DRA function, although we saw no clear changes to the DRA-mediated absorptive oxalate flux, JmsOx [175].…”
Section: Gut Microbiota and Oxalate Homeostasismentioning
confidence: 87%
“…Thus, the reductions in urinary oxalate in animals colonized with B. animalis occurred solely by intraluminal oxalate degradation. It is notable here that Kumar et al [176] looked at three other strains of Bifidobacteria and reported an increased expression of DRA in both mice and Caco-2 cells. This work focused on Cl − uptake by Caco-2 monolayers using a surrogate tracer ( 125 I) to show an approximate twofold induction of DRA function, although we saw no clear changes to the DRA-mediated absorptive oxalate flux, JmsOx [175].…”
Section: Gut Microbiota and Oxalate Homeostasismentioning
confidence: 87%
“…DRA mRNA and protein levels can be upregulated in response to anti-inflammatory agents, such as butyrate and probiotics (Lactobacillus acidophilus, Bifidobacterium sp.) (1,19,29), suggesting that the microflora, which is more abundant in the proximal colon, may have played a role. To this end, broad-spectrum antibiotic treatment normalizes the K8 Ϫ/Ϫ colitis (11).…”
Section: Discussionmentioning
confidence: 99%
“…Gene specific primers used are listed in Table 1. Gene expression levels were normalized to GAPDH (19).…”
Section: ϫ/ϫmentioning
confidence: 99%
“…This price gap has greatly expanded, and 125 I − is now >1/500th the cost of 36 Cl − . More recently, 125 I − has been used to measure Cl − –HCO 3 − exchange activity and Cl − absorption by cultured Caco‐2 cells (Gujral et al., ; Kravtsov et al., ; Kumar et al., ) and everted gut sacs of mouse large intestine (Saksena et al., ), respectively. However, neither reported a direct comparison of I − with Cl − and, although the latter study was the first instance in which 125 I − was used to examine Cl − transport by epithelia, it presented only a single unidirectional flux.…”
Section: Introductionmentioning
confidence: 99%